2022
DOI: 10.1038/s41598-022-08668-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial nanocomposite adsorbent based on poly(meta-phenylenediamine) for remediation of lead (II) from water medium

Abstract: In this study, poly(m-phenylenediamine)@ZnO (PmPDA@ZnO) nanocomposite was fabricated by in-situ chemical oxidative polymerization for the effective lead(II) removal from aqueous solutions. PmPDA@ZnO was characterized by several instrumental methods like FTIR, XRD, EDX, TGA, FESEM, TEM, zeta potential, and BET. The TEM images showed a core–shell-like structure for the PmPDA@ZnO nanocomposite. TGA results showed that the thermal stability of the PmPDA@ZnO nanocomposite was higher than the PmPDA. The maximum adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In this context, several adsorbents have been developed and tested for their efficiency in removing different pollutants [ 6 , 12 , 29 ]. The dynamic adsorbents are based on activated carbon [ 30 ], activated alumina [ 31 ], inorganic minerals [ 32 ], biomass adsorbents [ 33 , 34 , 35 , 36 , 37 , 38 ], polymer [ 39 , 40 , 41 ], carbon nanotubes (CNTs) [ 42 , 43 , 44 ] graphene oxide [ 45 , 46 ], metal-organic frameworks [ 47 ], microplastics [ 48 ] and more. Among these, CNTs based adsorbents are particularly interesting because their unique physical and chemical properties are relevantly suitable for adsorption [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several adsorbents have been developed and tested for their efficiency in removing different pollutants [ 6 , 12 , 29 ]. The dynamic adsorbents are based on activated carbon [ 30 ], activated alumina [ 31 ], inorganic minerals [ 32 ], biomass adsorbents [ 33 , 34 , 35 , 36 , 37 , 38 ], polymer [ 39 , 40 , 41 ], carbon nanotubes (CNTs) [ 42 , 43 , 44 ] graphene oxide [ 45 , 46 ], metal-organic frameworks [ 47 ], microplastics [ 48 ] and more. Among these, CNTs based adsorbents are particularly interesting because their unique physical and chemical properties are relevantly suitable for adsorption [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the FESEM image of the Fe 3 O 4 /CuO sample, a semi-spherical structure with a large concentration of nanoparticles can be noticed. Polymer morphology is widely recognized to be influenced by a variety of parameters such as acidity, monomer-to-initiator ratio, synthesis method, temperature, and others [ 36 ]. As a result, every parameter change might result in a change in the structural morphology of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…They found that PACPNS can be used as an efficient absorbent for removing lead (II) from aqueous media. In addition, poly (m-phenylenediamine)@ ZnO (PmPDA@ ZnO) nanocomposite prepared by in situ chemical oxidation polymerization can also effectively remove lead (II) in an aqueous solution [21]. Biochar Fe-Mn-Ce oxidemodified biochar composite adsorbents have the ability to remove arsenic from water [22].…”
Section: Introductionmentioning
confidence: 99%